Workplace Misconduct and Productivity: Exploring the Effects of Abusive Supervision and Sexual Harassment on Employee Productivity in Nigerian Private Enterprises - Olaoye, Samson Olukunmi (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Workplace misconduct continues to pose a significant challenge with widespread effects on employee well-being and organizational performance. This research explores the impact of abusive supervision and sexual harassment, two common forms of misconduct, on employee productivity within private enterprises in Nigeria. Drawing from Feminist Theory and Organizational Justice Theory, a qualitative approach was used to examine the experiences of employees at three prominent companies (MTN Nigeria, Shoprite, and Guaranty Trust Bank). Through in-depth interviews, it was revealed that both abusive supervision and sexual harassment lead to reduced productivity and negative consequences for employees. Victims expressed feelings of demoralization, increased stress, higher rates of absenteeism, and diminished job performance as a result of these behaviors, aligning with existing literature. Participants shared various coping mechanisms, such as avoidance, endurance, and formal reporting. The study emphasized the sense of powerlessness, unfairness, and the crucial role of organizational support. Findings were analyzed from feminist and justice perspectives, highlighting how power dynamics and perceptions of fairness influence outcomes. The research concluded with recommendations for Nigerian enterprises to enforce strict anti-harassment policies, provide ethical leadership training for supervisors, bolster reporting systems, and foster a culture of respect and fairness to safeguard employees, improve productivity, and uphold justice in the workplace.